The Optimization of PCI Interference in the 4G LTE Network in Padang - Dikky Chandra; - Zurnawita; Sri Yusnita; Dwiny Meidelfi; Andre Febrian Kasmar (Politeknik Negeri Padang, 2021)
With the growth of the customers and the expansion of the 4G LTE network in the area of Padang City, a PCI (Physical cell identity) modulo interference spot has been detected. PCI modulo interference occurs when an area is covered by two or more cells, which have a strong signal, and these cells have the same PCI modulo value. Based on the measurement results by the driving test method, the network conditions were not optimal because the SINR percentage (Signal to Interference Noise Ratio) in the good category was still low, at 9.47%, and the download throughput in the good category was 18.94%. This indicated that the interference in the area was quite high. Thus, it was necessary to do optimization action. The optimization action was taken by rotating the PCI on the site by considering the modulo value of each site so that the PCI with the same modulo did not merely lead to one location. Besides, action was taken to change the azimuth direction of cells that were too dominant. Based on the optimization process that has been carried out and the driving test activities that have been carried out again, the performance in the existing conditions has increased. The SINR percentage in the good category increased by 10%, so it became 19.47%, and the download throughput in the good category increased by 44.74% and became 63.68%.